Walking the walk through the open door: Realising Open Science infrastructures - Emma Norris; Maya Braun; James Green; Paquito Bernard; Gjalt-Jorn Peters (European Health Psychologist, 2026)
This article summarises the 2025 roundtable ‘Walking the way through the open door: realising open scienceinfrastructures’ held at the 2025 European Health Psychology Society Annual Conference. The roundtable aimed to identify perceived barriers to open infrastructure within the EHPS community, identify functionalities in closed software that the EHPS community value and how we can implement these in open infrastructure, and explore how we can ensure open infrastructure in health psychology. Our discussions in this roundtable and this article highlight the important role of institution and policy changes over individual researcher behaviour regarding open infrastructure. Moreover, we offer specific recommendations to increase adoption and sustainability of open infrastructure based on the Pyramid of Culture Change model/framework.